Concomitant effects of late fetal growth restriction and intra-cytoplasmatic sperm injection on fetal cardiac remodelling: a case report - Mappa, Ilenia; Luviso, Maria; Maqina, Pavjola; Rizzo, Giuseppe (Prenatal Cardiology, 2020)
Fetuses conceived by intra-cytoplasmatic sperm injection (ICSI) and complicated by fetal growth restriction (FGR) are characterised by a different phenotype of cardiac remodelling. We present a case in which both conditions, ICSI and late FGR, were present. An echocardiographic study of the fetal cardiac geometry showed the presence of a globular heart with sphericity indices of both ventricles values < 5th centile, not associated with dilated heart, as present in ICSI fetuses. The possible pathophysiological changes of these findings are discussed.